Mediasi Sebagai Pilihan Penyelesaian Perselisihan - Djumardin - (Jatiswara, 2015)
Under the terms of Article 16 paragraph (2) of Law No. 4 of 2004 on Judicial Power stated that the Court does not rule out the possibility for businesses in the peace settlement of civil cases (mediation). Peace institute in Article 130 HIR / 154 RBg in practice run by the Judges as a mere formality, not functioning optimally . As a result, the number of civil cases that enter and must be resolved and decided by the District Court the longer the number is increasing and becoming the burden of the Supreme Court . Hence the birth of PERMA No. 01 of 2008 on Mediation in the Court procedure is part of efforts to reduce the burden on the justice sector in Indonesia .